Predictors of Client Satisfaction Among Recent Users of Health Services in Lagos, Nigeria - Modupe Rebekah Akinyinka; Esther Oluwakemi Oluwole; Olumuyiwa Omotola Odusanya (SAGE Publishing, 2020)
Client satisfaction is an important measure of quality of care as it provides information on how well health service providers meet clients' values and expectations. The study was cross-sectional and analytical in nature. Data were obtained with the use of an interviewer-administered questionnaire. Respondents (n = 994) were a subset of a larger group of community members recruited for a study on quality of health care who had used a health facility for care within 3 months prior to data collection. A total of 94% of clients were satisfied with services received although client satisfaction rates were higher with private than public health facilities. Waiting time of less than 20 minutes (adjusted odds ratio [AOR] = 9.35, 95% confidence interval [CI] = 2.08-41.67), cheap cost of all services received (AOR = 7.58, 95% CI = 1.95-29.41), and the ability of the health care provider to offer explanations clearly to clients (AOR = 6.21, 95% CI = 1.90-20.41) were predictors of client satisfaction. However, the use of a government-owned hospital (AOR = 0.23, 95% CI = 0.08-0.63) was predictive of client dissatisfaction. Only service characteristics were predictive of client satisfaction. Improvement in service delivery is recommended.